2015
DOI: 10.1016/j.seizure.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Role of the gluten-free diet on neurological-EEG findings and sleep disordered breathing in children with celiac disease

Abstract: According to our preliminary data, in the presence of unexplained EEG abnormalities and/or other neurological disorders/SDB an atypical or silent CD should also be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 14 publications
4
46
2
3
Order By: Relevance
“…This broader view of the disease seen as an inflammatory disease is supported by clinical observations of extra-intestinal manifestations such as dermatological, hepatic, osteological, endocrine and neurological signs (57) . The most severe neurological symptoms are dementia, amnesia, ataxia, acalculia, epilepsy, chronic neuropathies, confusion, personality changes (58) , cognitive deficits (59) , multifocal encephalopathy, neuromyelitis optica, muscular hypotonia, delayed motor development (60) and headaches (61,62) , some of which could improve with GFD treatment (61,63) . Due to high levels of antigliadin antibodies, CD is seen as the common cause of neurological syndromes, particularly cerebellar ataxia, whose origin remains unknown.…”
Section: Neurological Complications and Cognitive Impairment In Coelimentioning
confidence: 99%
See 1 more Smart Citation
“…This broader view of the disease seen as an inflammatory disease is supported by clinical observations of extra-intestinal manifestations such as dermatological, hepatic, osteological, endocrine and neurological signs (57) . The most severe neurological symptoms are dementia, amnesia, ataxia, acalculia, epilepsy, chronic neuropathies, confusion, personality changes (58) , cognitive deficits (59) , multifocal encephalopathy, neuromyelitis optica, muscular hypotonia, delayed motor development (60) and headaches (61,62) , some of which could improve with GFD treatment (61,63) . Due to high levels of antigliadin antibodies, CD is seen as the common cause of neurological syndromes, particularly cerebellar ataxia, whose origin remains unknown.…”
Section: Neurological Complications and Cognitive Impairment In Coelimentioning
confidence: 99%
“…A recent study evaluated the role of a GFD on neurological symptoms, EEG characteristics and sleep breathing disorders (SBD) in children with CD (61) . The authors enrolled nineteen children with a new biopsy CD diagnosis.…”
Section: Neurological Complications and Cognitive Impairment In Coelimentioning
confidence: 99%
“…Use of antiepileptic drugs together with gluten-free diet may decrease frequency of epileptic attacks 4,5,16 . On the other hand, it was reported that EEG abnormalities improved in a child only with gluten-free diet after 6 months 15 . We found that EEG abnormalities improved in 3 of 4 patients with gluten-free diet and use of antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, there may be EEG abnormalities in absence of convulsions in CD 2 . It was reported that 48% of children with CD might have abnormal EEG findings 15 . We found this rate as 7.7% in our study, however we did not observe convulsions in any of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…При повторном обсле-довании через 6 мес. соблюдения строгой безглютеновой диеты изменения на ЭЭГ исчезли у 77,1% пациентов [19]. Аналогичная работа была проведена турецкими авторами.…”
unclassified